Epidural bupivacaine with or without ketamine for posoperative analgesia after abdominal hysterectomy. - Karki, Shambhu Bahadur (2000)
ABSTRACT: Objective: To assess the analgesic potentiation of epidural bupivacaine with 25 mg of ketmine in abdominal hysterectomy. Design: This study is prospective double blind randomized control study of epidural bupivacaine with or without addition of ketamine in abdominal hysterectomy. Patient was assessed in postoperative ward for 24 hours for the duration of postoperative analgesia, postoperative pain, analgesic requirement, haemodynamic changes and any complications. Patients and Method: patients undergoing abdominal hysterectomy under general anesthesia between age of 24-60 years, weight of 34-68 kg and ASA grade of I and II were selected for study. Patients were divided randomly into two groups A and B and investigated. Gorup A received 10mls of 0.25% bupivacaine epidurally and group B received same solution with addition of 25mg (0.5 ml) preservative free ketamine. Main outcome measures: Duration of postoperative analgesia, pain scores and requirement of additional analgesia were assessed in postoperative ward for 24 hours. Haemodynamic changes respiratory function and complications were also noted. Result: The postoperative analgesia was prolonged and less top-up was received in ketamine group, but the didference was not statistically significant. Changes in hemodynamics and respiratory rate were also not significant between the two groups. Level of pain scores, significantly less in group B after 6 hours of surgery, measured after cough and on pressure where P-va;ie was 0.01, but other pain scores were statistically not significant. Nausea and Vomiting were seen in both groups. There were no complications associated with ketamine. Conclusion: Epidural analgesia was very effective in intraoperative and postoperative period, It gives better analgesia without any sedation. Addition of ketamine in epidural bupivacaine has some beneficial effect, but it was not statistically significant. The incidence of postoperative Vomiting was high in ketamine group. Key words:Anaesthetic technique; epidural Analgesics;ketamine Local anaesthetic; bupivacaine Pain; postoperative.